Experimental study on the use of rejuvenators and plastomeric polymers for improving durability of high RAP content asphalt mixtures. (30th November 2017) - Bonicelli, Alessandra; Calvi, Paolo; Martinez-Arguelles, Gilberto; Fuentes, Luis; Giustozzi, Filippo
Highlights: High RAP mixes, with rejuvenator and polymer, can achieve good mechanical properties. The optimal proportioning of additives depends on weather and binder properties. The optimal mix selection should depend on a cost/performance analysis. A statistical analysis of the results was conducted. Abstract: The use of RAP (Reclaimed Asphalt Pavement) in new asphalt pavements could potentially generate environmental footprint reduction especially in terms of raw-material consumption. This investigation aims to evaluate the effectiveness of the addition of rejuvenator and plastomeric polymer on the performance of high RAP content (40%) asphalt mixture. Six combinations, varying proportion of rejuvenator and polymer, were studied. Mechanical and long-term performance was evaluated through laboratory investigations analyzing the physical properties and rheology of the binder and measuring stiffness modulus and permanent deformations (rutting) of recycled asphalt mixes. Outcomes showed that a proper calibration of rejuvenation agent and polymer can enhance the overall durability of high RAP content mixes. Statistical analysis of results was also conducted to determine the significance of variables involved.